CircRNA-Mediated Regulation of Angiogenesis: A New Chapter in Cancer Biology - Jiang, Shaotao; Fu, Rongdang; Shi, Jiewei; Wu, Huijie; Mai, Jialuo; Hua, Xuefeng; Chen, Huan; Liu, Jie; Lu, Minqiang; Li, Ning (Frontiers in Oncology, 2021)
Angiogenesis is necessary for carcinoma progression and is regulated by a variety of pro- and anti-angiogenesis factors. CircRNAs are RNA molecules that do not have a 5'-cap or a 3'-polyA tail and are involved in a variety of biological functions. While circRNA-mediated regulation of tumor angiogenesis has received much attention, the detailed biological regulatory mechanism remains unclear. In this review, we investigated circRNAs in tumor angiogenesis from multiple perspectives, including its upstream and downstream factors. We believe that circRNAs have natural advantages and great potential for the diagnosis and treatment of tumors, which deserves further exploration.